2021
DOI: 10.2478/acve-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro Activation of Bovine Endometrial and Vaginal Epithelial and Blood Mononuclear Cells to Produce Nitric Oxide in Response to Mycoplasma bovis, Mycoplasma bovigenitalium and Ureaplasma diversum

Abstract: Genital mycoplasmosis is a condition present in bovine production systems, and the most important agents involved are Mycoplasma bovis, Mycoplasma bovigenitalium and Ureaplasma diversum. Some aspects of their pathogenesis remain unclear. This study was designed in order to evaluate their ability to stimulate mononuclear cells from the endometrium, vagina and peripheral blood of cycling and healthy cows to produce nitric oxide (NO). Cellular cultures of endometrial, vaginal and peripheral blood cells from 33 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Our data revealed that bovine PBMC cultures incubated with rGUDIV-103 for 2 and 6 h induced NO and H 2 O 2 production and iNOS expression. Many other Mollicutes, LAMP extracts, and recombinant LAMPs induce NO and H 2 O 2 production in cellular models [ 74 , 75 ]. NO is a multifunctional molecule involved in several physiological and pathological processes and often plays a dual concentration-dependent role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data revealed that bovine PBMC cultures incubated with rGUDIV-103 for 2 and 6 h induced NO and H 2 O 2 production and iNOS expression. Many other Mollicutes, LAMP extracts, and recombinant LAMPs induce NO and H 2 O 2 production in cellular models [ 74 , 75 ]. NO is a multifunctional molecule involved in several physiological and pathological processes and often plays a dual concentration-dependent role.…”
Section: Discussionmentioning
confidence: 99%
“…U. diversum induces NO production in peritoneal macrophage cultures, associated with a pro-inflammatory cytokine profile [ 76 ]. On inoculation with U. diversum , cells from the bovine endometrium, vagina, and peripheral blood produce NO, suggesting that these cells play a role in the immediate response to Ureaplasma infection [ 75 ]. Low NO concentrations protect cells from apoptosis, whereas excessive NO production triggers apoptosis in several cell types [ 74 , 77 ].…”
Section: Discussionmentioning
confidence: 99%